2022
DOI: 10.3389/fnut.2022.963598
|View full text |Cite
|
Sign up to set email alerts
|

Poria cocos polysaccharide prevents alcohol-induced hepatic injury and inflammation by repressing oxidative stress and gut leakiness

Abstract: Alcoholic liver disease (ALD) is a major worldwide chronic liver disease accompanied by hepatic inflammation, gut leakiness, and abnormal oxidative stress. Our previous study demonstrated substantial hepatoprotective activity of the active Poria cocos polysaccharide (PCP-1C). The present study explored whether PCP-1C protects against ALD among hepatic inflammation, gut leakiness, and abnormal oxidative stress. The results showed that PCP-1C significantly improved alcohol-induced liver injury by decreasing seru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 41 publications
0
8
0
Order By: Relevance
“…Ma et al [ 33 ] found that knockdown or inhibition of the p38 gene attenuated the aggravation of neutrophil infiltration and alleviated liver injury and inflammation in an acute-on-slow alcohol-fed mice model, indicating that p38 plays a key role in slow-on-acute alcohol-fed liver injury. The study results of Jiang et al [ 34 ] showed that Poria cocos polysaccharide (PCP-1C) could reduce liver inflammation by inhibiting MAPK signaling pathway. This suggests that the downregulation of this signal may be a way to prevent inflammation in the liver.…”
Section: Discussionmentioning
confidence: 99%
“…Ma et al [ 33 ] found that knockdown or inhibition of the p38 gene attenuated the aggravation of neutrophil infiltration and alleviated liver injury and inflammation in an acute-on-slow alcohol-fed mice model, indicating that p38 plays a key role in slow-on-acute alcohol-fed liver injury. The study results of Jiang et al [ 34 ] showed that Poria cocos polysaccharide (PCP-1C) could reduce liver inflammation by inhibiting MAPK signaling pathway. This suggests that the downregulation of this signal may be a way to prevent inflammation in the liver.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, polysaccharides have attracted wide-spread attention for their physiological properties, such as anti-virus [ 73 ], anti-tumor [ 74 ], anti-inflammatory [ 75 ], anti-diabetic [ 76 ], anti-liver injury [ 77 , 78 , 79 , 80 , 81 ], reducing obesity [ 82 ], and immune regulation [ 83 ]. Polysaccharides have become one of the current research hotspots owing to the prevention and treatment of liver damage in various ways (e.g., anti-inflammatory, anti-apoptotic, anti-oxidative stress) [ 84 , 85 , 86 , 87 ].…”
Section: Ameliorative Effects Of Polysaccharides On Nafld Via the Gut...mentioning
confidence: 99%
“…The value of Mw/Mn was close to 1, which indicates that PCP-1C was relatively homogeneous. Further experiments showed that PCP1C had excellent anti-inflammatory and antioxidant activity [ 19 ]. However, whether it is possible to use PCP1C with higher purity to prepare polysaccharide iron and how its physiological activity needs to be further studied.…”
Section: Introductionmentioning
confidence: 99%